The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1159/000083660
|View full text |Cite
|
Sign up to set email alerts
|

The Nephrotoxin Ochratoxin A Induces Key Parameters of Chronic Interstitial Nephropathy in Renal Proximal Tubular Cells

Abstract: Ochratoxin A (OTA) is a nephrotoxic and cancerogenic mycotoxin. There is epidemiological evidence that OTA exposition leads to cortical interstitial nephropathies in humans. However, virtually no data are available investigating the effect of OTA on renal cortical cells with respect to induction of nephropathy. Thus, we investigated whether OTA is able to induce changes of cellular properties potentially leading to interstitial nephropathy, using proximal tubular cell lines (OK, NRK-52E). OTA decreased cell nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 34 publications
4
47
1
Order By: Relevance
“…Some other studies also confirmed OTAinduced MAPK phosphorylation (5,24,25,28). Phosphorylation of ERK1/2 and of their substrates Elk-1 and p90RSK was observed in kidney samples of male Fischer 344 rats fed with a carcinogenic dose of OTA over 7 days, 21 days, and 12 months (24).…”
Section: Close Interplay Between Ota and Mapksmentioning
confidence: 66%
See 4 more Smart Citations
“…Some other studies also confirmed OTAinduced MAPK phosphorylation (5,24,25,28). Phosphorylation of ERK1/2 and of their substrates Elk-1 and p90RSK was observed in kidney samples of male Fischer 344 rats fed with a carcinogenic dose of OTA over 7 days, 21 days, and 12 months (24).…”
Section: Close Interplay Between Ota and Mapksmentioning
confidence: 66%
“…According to the European survey conducted by Miraglia et al (2), mean plasma concentration of OTA in adults is 0.875 nmol L -1 , and ranges from 0.53 nmol L -1 to 2.75 nmol L -1 . OTA half-life in serum ranges from 120 h in rats to 840 h in monkeys and humans (4,5). This prolonged retention in serum is the consequence of strong binding to serum proteins, mainly to albumin.…”
Section: Ochratoxin A: a Hazardous Mycotoxinmentioning
confidence: 99%
See 3 more Smart Citations